Developing feminist analyses: Burman, E, Alldred, P, Bewtey, C, Goldberg, B, Heenan, C, Marks, D, Marshall, J, Taylor, K, Ullah, R & Warner, S (1996) Challenging women: Psychology’s exclusions, feminist possibilities. Buckingham: Open University Press. ISBN 0-335-19510-5. 210 pages. - Straker, Gill (PINS-Psychology in Society, 2026)
As is demanded by the genre within which Challenging women is written, I will position myself as a reviewer and in this regard, it would seem that being a South African psychologist is more important than the usual markers of being white, middle class and female. As a South African psychologist, like many of my colleagues, I embrace social constructionism and discourse analysis and therefore do not need to be convinced of its insights. Why it should be so that psychologists in particular contexts embrace or fail to embrace constructionism, is one of the themes of Challenging women which locates psychology in its macro-context. In this regard it is of note that in South Africa in the 1970s and 1980s the turbulent political macro-context was such that psychology was forced to either question its relevance and its power relations or to take refuge in an ever deepening fundamentalism concerning its truth claims, based on theoretical notions of essentialism in regard to race and gender and on methodologies aspiring to remain faithful to the "scientific" method Given this choice many South African psychologists at this time took the risk of questioning the discipline and found in discourse analysis a very helpful tool, although how successful we have been in generating alternatives to mainstream psychology is a moot point.